2019
DOI: 10.1080/24749508.2019.1568129
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the sodium absorption ratio using data-driven models: a case study in Iran

Abstract: In this investigation, two data-driven models, i.e., Gaussian Process (GP) and Support Vector Machine (SVM), were used to predict the sodium absorption ratio (SAR) in three subwatersheds (Khorramabad, Biranshahr, and Alashtar) in Iran. A comparison was also done with these data-driven models with Artificial Neural Network (ANN). The parameters total dissolved solids, electrical conductivity, pH value, CO 3 , HCO 3 , chlorine (Cl), SO 4 , calcium (Ca), magnesium (Mg), sodium (Na), and potassium (K) were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The SAR indicator is calculated by measuring the concentrations of sodium, calcium, and magnesium in the soil and using the following equation: SAR= italicNa/12Ca+Mg (Singh, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The SAR indicator is calculated by measuring the concentrations of sodium, calcium, and magnesium in the soil and using the following equation: SAR= italicNa/12Ca+Mg (Singh, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…ANN, a concept taken from the human mind, is a widely used prediction technique (Sepahvand et al 2019;Sihag et al 2020;Singh 2020). ANN has a brain like architecture and neuron system.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…They indicated the robustness of these algorithms to support the decision-making process for sustainable crop yield. [9] employed SVM and Gaussian process regression (GPR) for the simulation of SAR in three sub-watersheds in Iran. These studies demonstrated the potential of AI and ML as a tool for predicting various water quality indices in irrigation systems and highlighted the importance of such predictions in improving water management practices and ensuring sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%